Numerical simulations of a confined channel flow driven by non-isothermal wall injection. (6th April 2006) - Fournier, C.; Michard, M.; Bataille, F.
The velocity and temperature fields of a confined channel flow driven by air injection through a porous wall are numerically investigated. The equations of the problem are modelled using a RNG k - ε and a RSM model. Furthermore, two models of blowing (sources model and holes model) are used. Results show a sudden increase of the velocity fluctuations which affect the mean velocity and temperature profiles. The two blowing models are compared, showing similar results even through the discrete nature of one of the model is visible. Finally, the effects of turbulence in the injected fluid are investigated.